2019
DOI: 10.1038/s41374-018-0134-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KLF14 protects against immune-mediated hepatic injury in mice

Abstract: The underlying immunopathogenic mechanisms of autoimmune hepatitis (AIH) have not yet been well elucidated. An impairment in regulatory T cells (Tregs) is key to the development of AIH. Krüppel-like factors (KLFs) regulate a broad of cellular processes including immunocyte maturation. KLF14 may regulate Treg differentiation, but the biological functions remain far from elucidated. In this study, we identified the hepatic expression of KLF14 in human and murine liver diseases. Immune-mediated hepatitis was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…17 However, another study yielded conflicting findings as to the role of KLF14 in Con A-induced mice hepatitis. 3 The study found that the expression level of KLF14 was decreased in AIH patients and experimental AIH mice models as compared to normal controls. KLF14 overexpression did not induce any significant change in Tregs, but the frequency of Tregs was increased after the mice transfected with the plasmid were challenged with Con A.…”
Section: Klf14 and Immune Regulationmentioning
confidence: 94%
See 3 more Smart Citations
“…17 However, another study yielded conflicting findings as to the role of KLF14 in Con A-induced mice hepatitis. 3 The study found that the expression level of KLF14 was decreased in AIH patients and experimental AIH mice models as compared to normal controls. KLF14 overexpression did not induce any significant change in Tregs, but the frequency of Tregs was increased after the mice transfected with the plasmid were challenged with Con A.…”
Section: Klf14 and Immune Regulationmentioning
confidence: 94%
“…These data suggested that KLF14‐induced differentiation of Treg was closely related to autoimmune inflammation in mice colitis . However, another study yielded conflicting findings as to the role of KLF14 in Con A‐induced mice hepatitis . The study found that the expression level of KLF14 was decreased in AIH patients and experimental AIH mice models as compared to normal controls.…”
Section: Klf14 and Immune Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The resuspended cells were processed with 30% Percoll (Sigma-Aldrich; Merck KGaA) and gently overlaid onto 70% Percoll. After density gradient centrifugation at 1,000 × g for 30 min, liver MNCs were harvested from the interface of the Percoll gradient (37). The MNCs collected were used for further fluorescence-activated cell sorting (FACS) analysis.…”
Section: Methodsmentioning
confidence: 99%